Public service motivation and prosocial motivation: two sides of the same coin?. Issue 7 (2nd July 2020) - Ritz, Adrian; Schott, Carina; Nitzl, Christian; Alfes, Kerstin
ABSTRACT: This study raises the important question of how public service motivation and prosocial motivation are related to one another and how, together, these two concepts affect behavioural outcomes of public employees. Based on a sample of 747 public employees and using partial least squares structural equation model, we analyse the relationships between public service motivation, prosocial motivation, and different behavioural outcome variables in a single model simultaneously. Our study shows that public service motivation and prosocial motivation are not only theoretically, but also empirically distinct concepts. This has important implications for the use of these concepts, as will be discussed.